AKAR PERMASALAHAN KONTROVERSI SEPUTAR TANGGUNG JAWAB SOSIAL PERUSAHAAN - ., Shidarta (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
The substance of corporate social [and environmental]responsibility as stipulated in Article 74 of Law No. 40 Year2007 on Limited Corporation has been creating controversies.Despite the huge pressures from many parties to annul thearticle, The Indonesian Constitutional Court concluded tomaintain it as a binding article and believed that its content isstill in line with the constitution. Accommodating CSR into ourlegal system can be considered a progressive step for the sakeof Indonesian people in majority, especially for those who havea very limited access to utilize our natural resources. On theother hand, many companies seem still reluctant to implementthe mandatory CSR although Article 74 possibly imposecriminal sanctions against the violaters. The author of thispaper believes that the controversial issues over CSR arelingering on several fundamental discourses, such as thedichotomies between morality and law, between responsibilityand liability, and between individual/public interest and socialinterest. He intends to discuss these dichotomies in theperspective of legal philosophy.